2006
DOI: 10.1007/s11295-006-0047-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the DELLA subfamily in apple (Malus x domestica Borkh.)

Abstract: The hormone gibberellic acid (GA) regulates growth and development throughout the plant life cycle. DELLA proteins are key components of the GA signalling pathway and act to repress GA responses. The "DELLA" amino acid motif is highly conserved among diverse species and is essential for GA-induced destruction of DELLA proteins, which relieves repression. Six genes encoding the DELLA motif were identified within an apple expressed sequence tag (EST) database. Full-length cDNA clones were obtained by RACE and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 75 publications
6
30
0
Order By: Relevance
“…DNA sequencing revealed that each product was composed of two GAI sequences, which we considered to have been derived from the alleles. These results indicate, as in other variety (Foster et al 2007), that the GAI genes in Malus species have no introns. By genomic walking and 5′-RACE, we fully sequenced GAI from "Fuji"-MdGAI1 (FJ535245) and MdGAI2 (GQ384423), and from M. x-MxGAI1 (FJ535244).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…DNA sequencing revealed that each product was composed of two GAI sequences, which we considered to have been derived from the alleles. These results indicate, as in other variety (Foster et al 2007), that the GAI genes in Malus species have no introns. By genomic walking and 5′-RACE, we fully sequenced GAI from "Fuji"-MdGAI1 (FJ535245) and MdGAI2 (GQ384423), and from M. x-MxGAI1 (FJ535244).…”
Section: Resultssupporting
confidence: 84%
“…The use of a transgenic plant expressing a reporter gene driven by the GAI promoter would clarify whether GAI is expressed exclusively in the phloem tissue or if mRNA expressed in surrounding tissues accumulates in the phloem, as do CONSTANS and FT mRNAs (An et al 2004). There are subfamily genes (Foster et al 2007) of GAI in apple corresponding to RGA and RGL in Arabidopsis (Lee et al 2002). Currently, no information is available on the transportability of these transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…In the grapevine Vvgai mutant, a correlation was observed between the DELLA-associated GA signaling pathway and inflorescence development (Boss and Thomas, 2002). Ectopic expression of MdRGL2a in Arabidopsis significantly delays flowering in short days (Foster et al, 2007). Similarly, transgenic tomatoes ectopically expressing the Mhgai1 gene produced compacted inflorescences containing smaller flowers, which were partially sterile and showed a decreased capacity to produce parthenocarpic fruits.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, ectopic expression of MdRGL2a causes GA-insensitive dwarfism in Arabidopsis (Foster et al, 2007). However, their functions in dwarfing rootstock are not yet clear.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a series of grafting experiments showed that DELLA gene mRNAs could be trafficked over long-distances via the phloem (Iqbal, Nazar, Khan, Masood, & Khan, 2011;Kim, Canio, Kessler, & Sinha, 2001;Wang et al, 2012), opening the possibility of rootstock containing GA-insensitive alleles of DELLA to dwarf the scion cultivars grafted on to them. Recently, among six DELLA genes isolated from the 'Royal Gala' apple cultivar (MdRGL1a/b, MdRGL2a/b and MdRGL3a/b), the ectopic expression of MdRGL2a has been shown to cause GA-insensitive dwarfism in Arabidopsis (Foster et al, 2007). MhGAI1 has been cloned from the apomictic tea crabapple (Malus hupehensis Redh.…”
Section: The Control Of Primary Growth and Shoot Elongationmentioning
confidence: 99%